Advancing entrepreneurial mindset: What do we know and where do we go?. (2nd January 2023) - McLarty, Benjamin D.; Hornsby, Jeffrey S.; Liguori, Eric W.
ABSTRACT: In this special issue of the Journal of Small Business Management we aim to explain why entrepreneurial mindset is at a critical juncture in its theoretical and practical development. Drawing on multiple conceptualizations, alternative definitions of the concept are proffered, and details regarding the six included manuscripts in the special issue are given to help explain how future research on entrepreneurial mindset should proceed. Additionally, specific future research directions are indicated given the recent global pandemic conditions and its likely impact on the formation of entrepreneurial mindset.